A public health community health worker-delivered intervention to reduce human trafficking among Denotified Tribes in India: A protocol paper - Meredith Dank; Sheldon Zhang; Stephen Abeyta; Lauren Moton; Hanni Stoklosa; Nani Cuadrado; Alex Dahlen; David J. Farabee (PLoS ONE, 2025)
The objective of this study is to evaluate an intervention designed to reduce human trafficking among Denotified Tribes (DNTs) in two regions of India. We will conduct a cluster-randomized controlled trial utilizing a participatory-designed, community health worker (CHW)- delivered public health intervention. CHWs will be trained to conduct anti-human-trafficking advocacy and psychological first aid (humane, supportive and practical assistance to people who are distressed) to DNT community members, and mobilize resources to ensure access to health and mental health services, education, livelihoods, and government benefits. This project leverages known effective, systemic, and sustainable approaches to reducing vulnerabilities to trafficking among DNT communities, through increased economic alternatives, health and mental health services guided by the trafficking-survivor-informed treatment protocols.